Doar exercitiul 6,multumesc.
Anexe:
Răspunsuri la întrebare
Răspuns de
1
a=√(4+2√3)=√(4+√12)=√[4+√(16-12)]/2+√[4-√(16-12)]/2=
=√(4+√4)/2+√(4-√4)/2=√(4+2)/2+√(4-2)/2=√3+1
Ix+√3I=a
x+√3 >0
Ix+√3I=x+√3=a
x+√3=√3+1
x=1
x+√3 <0
Ix+√3I=-x-√3=a
-x-√3=√3+1
x=-2√3-1
=√(4+√4)/2+√(4-√4)/2=√(4+2)/2+√(4-2)/2=√3+1
Ix+√3I=a
x+√3 >0
Ix+√3I=x+√3=a
x+√3=√3+1
x=1
x+√3 <0
Ix+√3I=-x-√3=a
-x-√3=√3+1
x=-2√3-1
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă